Organisation theory in education: how does it inform school leadership? - Bush, Tony (American Educational Research Association, 2015)
Much of the literature treats organisation and leadership theories as distinct and unconnected but, in this paper, I argue that there are considerable overlaps between these two genres of theory. In particular, I seek to demonstrate that organisation and leadership theory can be analysed and compared using four central constructs: goals, structure, culture and context. In this paper, I begin by discussing the origins of organisation theory and then examine its characteristics through a discussion of the four constructs. The main school leadership models are examined and then linked to organisation theory through the four constructs. The paper concludes with an overview of the connections between leadership and organisation theory.